The Image of the Garden in the Creativity of Ravil Bukharaev and Lydia Grigorieva in the Context of Dialogue of Cultures - Kamalieva, Regina R.; Ibragimov, Marsel I.; Galimullina, Alfiya F.; Nickolsky, Evgeny V. (Journal of History Culture and Art Research, 2017)
One of the research aspects in this direction is considered in this article: the question of semantic and functional features of the garden image in Ravil Bukharayev and Lydia Grigorieva's poetry. The concept of dialogue of cultures which allows considering the garden image in Bukharayev and Grigorieva's poetry in the aspect of semiosis and broad inter-textual communications including various texts and cultural codes which are present in them became the basis of this research. Having considered specifics of artistic realization of the garden image in Bukharayev and Grigorieva's creativity authors of article came to the following conclusions: there are essential differences in attitudes of the poets reflected in their art creativity. If for R. Bukharayev the image of a garden as a rule is associated with the homeland, the native language from which isolation is sharply experienced by the poet (in the cycles "Kazan Snow", "Agony in the Garden", etc.), then Grigorieva organically fits into the English literary environment, its acceptance of the English world, cultures occurs without visible efforts, is harmonious and creative. Grigorieva learns philosophy of garden not only by means of traditional poetic means of expression, but also creating and proving the new synthetic genre determined by it as "film poetry", "photo poetry".